Strategi Komunikasi BPBD dalam Penanganan Bencana Banjir Kampung Lalang Medan Sumatera Utara - Aisyah Putri; Annisa Nabilah Br Ginting; Dika Sutryani; Rahmanita Ginting (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Flooding is one of the most frequent hydrometeorological disasters in urban areas in Indonesia and causes significant social, economic, and humanitarian impacts (BNPB, 2024). Medan City, particularly the Kampung Lalang area in Medan Sunggal District, is an area that experiences repeated flooding due to high rainfall intensity and overflowing of the Deli, Babura, and Sunggal watersheds. Data from the Deli Serdang Regional Disaster Management Agency (BPBD) in November 2025 recorded 16 fatalities, 40,094 houses submerged, and 207,441 people affected by flooding and landslides in the Medan area. Meanwhile, the Medan City BPBD reported that 3,181 houses and 10,391 people were affected by flooding in October 2025 with no fatalities. In disaster situations, communication plays a strategic role as a means of coordination, conveying emergency processes, and raising public awareness of disaster management policies. The Medan City BPBD serves as a disaster communication command center that coordinates information between agencies, volunteers, and affected communities. This study aims to analyze the communication strategy of the Regional Disaster Management Agency (BPBD) in handling the flood disaster in Kampung Lalang, focusing on the role of communicators, coordination patterns, and obstacles in disseminating messages to the community. This study uses a qualitative descriptive approach through interviews, observations, and documentation studies. The results indicate that the effectiveness of the BPBD's communication strategy is influenced by the credibility of the communicators, the clarity of information flow, and synergy between agencies. However, challenges remain, such as low community risk literacy and the complexity of field conditions in flood-prone areas.